Speciation and stable isotopic compositions of humic sulfur in mud sediment of the East China Sea: Constraints on origins and pathways of organic sulfur formation - Zhu, Mao-Xu; Huang, Xiang-Li; Yang, Gui-Peng; Hao, Xiao-Chen (Organic geochemistry, 2013)
•Contents and sulfur isotopes of three organic sulfur (OS) forms are investigated.•Hydrolyzable OS is almost biological in origin and diagenetically refractory.•Terrigenous OS accounts for 77–79% of HA-S and sulfurization for 41–71% of FA-S.•Humic-acid S is generally inert in early diagenesis, but fulvic-acid S is reactive.•Low humic-sulfur in the sediment is due to a low extent of sulfurization. Humic sulfur is commonly the most important pool of organic sulfur (OS) in marine sediments and also important for the budget of total sedimentary sulfur. In this study, contents and stable sulfur isotopic compositions of hydrolyzable organic sulfur (HYOS), humic acid sulfur (HA-S) and fulvic acid sulfur (FA-S) in one core collected from the East China Sea (ECS) inner shelf were determined to investigate the sources and pathways of OS formation and to compare diagenetic geochemistry of HA-S and FA-S. HYOS in the core is essentially biological in origin and diagenetically refractory, with a fairly low fraction of labile sulfur bearing biomolecules. HA-S in the core is largely terrigenous residual bio-OS, while FA-S is a mixture of marine bio- and diagenetic OS (diag-OS), with the diag-OS fractions between 44% and 71%. Both HA-S and FA-S contents in the core are at the lower ends of the corresponding values reported in the literature. The HA in the sediments is diagenetically inert, subject to neither significant diagenetic sulfurization nor bio-OS mineralization loss, while the FA is reactive, prone to both sulfurization and decomposition loss of diagenetically bound OS. Low contents of humic S [i.e., ∑(HA-S+FA-S)] in the core may suggest that OS burial has only minor contribution to the burial of total sulfur in the sediments due to generally low OM sulfurization.